Malnutrition Risk Among Chronic Kidney Disease Patients Attending the Nephrology Clinic in Hospital Tengku Ampuan Afzan, Pahang - Sowtali, Siti Noorkhairina; Mohd Rasani, Ali Aminuddin; Mohd. Yusoff, Dariah; Mohd. Shah, Azarisman Shah; Draman, Che Rosle; Harith, Sakinah; Zainol, Nurul Alia Jasmin; Mohd. Zuki, Nurul Atikah; Md. Nawi, Nur Izzati (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2021)
Objective: The prevalence of chronic kidney disease among adult in Malaysia has been increasing and it is forecasted that the pattern will remain. The risk for malnutrition is prominent especially in the later stage of chronic kidney disease. Early detection of malnutrition is important to prevent further complications. However, limited studies on malnutrition risk has been conducted in Malaysia. Therefore, this study was performed to determine the prevalence and associated risk factor of malnutrition among chronic kidney disease patient attending Nephrology Clinic in Hospital Tengku Ampuan Afzan, Kuantan, Pahang. Methods: A cross-sectional study was conducted among 70 chronic kidney disease patients using convenience sampling. All patients were explained about the study and informed consent obtained prior the administration of questionnaire. There were three parts of questionnaire to be answered which were on sociodemographic, clinical characteristic and dietary information along with Malnutrition Risk Screening Tool-Hospital to measure the risk for malnutrition. Results: Most of the participants were married (75.7%), had completed primary school (58.6%), currently not working (32.9%), had income between RM 1000 to RM 1999 (37.1%) and living with three or four members in a household (24.3%). Majority had at least one precipitating disease that causes chronic kidney disease such as hypertension (71.4%) followed by diabetes (61.4%) and high cholesterol (30.0%). Almost 21.4% of chronic kidney disease patients screened were at risk for malnutrition. Further inferential analysis shows an association between weight loss (p=0.001) towards risk for malnutrition. Conclusion: Overall, the risk for malnutrition among chronic kidney disease patient was fairly high. This warrant close attention of the healthcare professional that caring for the patients particularly in detection of detrimental weight loss during each follow up visit. A referral to the dietician is important to ensure the patients received adequate counselling and education on dietary management.